2016
DOI: 10.1002/mnfr.201600257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yuja peel extract and its flavanones on osteopenia in ovariectomized rats and osteoblast differentiation

Abstract: Dietary YPEE has a protective effect on OVX-induced osteopenia. YPEE and its flavanones promote osteoblastogenesis via the activation of the BMP/p38/Smad/Runx2 pathways. These results extend our knowledge of the beneficial effects of YPEE and provide a basis for the development of novel therapies for osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Taken together, the micro-CT analysis indicated that NM attenuated OVX-induced osteoporosis. Bone regeneration is related to an induction of osteoblast cell proliferation, ALP activation, intracellular Ca deposition, mineralization and extracellular matrix formation [49][50][51]. As shown in Figure 2A, 250-1000 µg/mL of NM increased ALP activity in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Taken together, the micro-CT analysis indicated that NM attenuated OVX-induced osteoporosis. Bone regeneration is related to an induction of osteoblast cell proliferation, ALP activation, intracellular Ca deposition, mineralization and extracellular matrix formation [49][50][51]. As shown in Figure 2A, 250-1000 µg/mL of NM increased ALP activity in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 90%
“…The present study showed that NM treated group could increase ALP activity and gene expression of the osteogenic makers RUNX2, osteocalcin, BMP-2, COL-1, Wnt3a, and p-SMAD 1/5/8. These osteoblast-related markers are participated in bone regeneration, formation, and metabolism [51,54,55]. In addition, a previous study on the effects of genistein on osteoblast-associated metabolism proved that genes related to the BMP/SMAD signaling pathway showed the strongest enhancements in human bone marrow stromal cell (hBMSC) cultures [53].…”
Section: Discussionmentioning
confidence: 99%
“…ALP is an important indicator of bone mineralization, an early biomarker for osteopenia, and is expressed by all osteoblastic cells [24]. The differentiated osteogenic cells exhibited increased ALP activity and enhanced bone mineralization [222324]. The present study showed that melanin significantly increased ALP activities concentration-dependently (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Bone regeneration induced osteoblast proliferation, increased ALP activity, and stimulated intracellular calcium deposition, extracellular matrix formation, and mineralization [2223]. ALP is an important indicator of bone mineralization, an early biomarker for osteopenia, and is expressed by all osteoblastic cells [24]. The differentiated osteogenic cells exhibited increased ALP activity and enhanced bone mineralization [222324].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental AAB group was administrated orally with 100 mg/kg of AAB daily. This dose of AAB was selected based on previous references regarding the effect of the medicinal herb on osteoporosis (17)(18)(19). The E2 group was intraperitoneally injected with 10 µg/kg E2 daily.…”
Section: Methodsmentioning
confidence: 99%